Malay Culture in Welcoming the Century of Artificial Intelligence Excellence - Safna Febriyani; Haris Riadi; Wan Azman; Suseno Suseno (Yayasan Keluarga Guru Mandiri, 2025)
The rapid development of artificial intelligence (AI) technology has brought human civilization into a new era known as the century of technological excellence. In this context, local cultures such as Malay culture face significant challenges and opportunities to remain relevant, adaptive, and sustainable amid disruptive digital modernization currents. This research aims to examine the position of Malay culture in the face of AI dominance and explore strategies for preservation, identity strengthening, and integration of cultural values into the future digital ecosystem. The method in this study is a descriptive qualitative approach with literature study, participatory observation, and in-depth interviews with cultural figures, academics, and technology-based creative industry players. The study results show that Malay culture has great potential to develop in line with AI through revitalizing local wisdom values such as syarak customs, Kitabullah sharia, buddhist philosophy, and the principles of deliberation and mutual cooperation. These values can be integrated into developing ethical algorithms, digital narratives, and AI-based educational systems rooted in local characters. However, there are significant challenges in the form of low digital literacy among the Malay community, limited technological resources, and the dominance of global content that does not represent local identity. Therefore, collaboration between educational institutions, governments, cultural communities, and technology actors is critical to creating an inclusive, humanistic, and culture-based AI ecosystem. This study concludes that Malay culture can survive and has an excellent opportunity to pioneer the creation of AI models based on local values. With the right strategy, the century of AI excellence is not a threat, but a momentum to display the uniqueness and wisdom of Malay culture on the global stage.